In their own voices : transracial adoptees tell their stories - Simon, Rita J. (Rita James), 1931-2013 (Columbia University Press, 2000)
Nearly forty years after researchers first sought to determine the effects, if any, on children adopted by families whose racial or ethnic background differed from their own, the debate over transracial adoption continues. In this collection of interviews conducted with black and biracial young adults who were adopted by white parents, the authors present the personal stories of two dozen individuals who hail from a wide range of religious, economic, political, and professional backgrounds. How does the experience affect their racial and social identities, their choice of friends and m.